Analysis of the formative assessment implementation and its challenges in high school biology learning - Alvi Anggraeni; Shefa Dwiyanti Ramadani; Ericka Darmawan (Inornatus: Biology Education Journal, 2026)
The implementation of formative assessment in biology learning at the senior high school level in Magelang City has not been widely explored. This study aims to analyze the implementation of formative assessment and identify the challenges faced by biology teachers. The study employed a descriptive qualitative approach involving biology teachers and ten senior high school students in Magelang City. Data were collected through questionnaires, interviews, and observations, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that formative assessment was implemented through information collection activities such as question-and-answer sessions, quizzes, and reflections, followed by information processing based on students’ level of understanding and minimum competency criteri, as well as follow-up actions in the form of remedial and enrichment activities. The implementation of formative assessment was categorized as good because it effectively monitored students’ understanding and positively contributed to learning outcomes and science process skills. However, several challenges were identified, particularly limited instructional time and inadequate facilities and infrastructure. This study highlights the importance of formative assessment in supporting effective biology learning and suggests strengthening infrastructure support, providing continuous teacher training, and enhancing collaboration among teachers, students, and parents to optimize its implementation.